A red-emitting luminescent probe for sequentially detecting Cu2+ and cysteine/histidine in aqueous solution and its imaging application in living zebrafish. (December 2020) - Yang, Yutong; Li, Yibin; Zhi, Xiaomin; Xu, Yingjun; Li, Minna
Abstract: A unique red-emissive luminescent probe based on dipicolyl amine (DPA) tethered ruthenium(II) tris (bipyridine) derivative (Ru-DPA) has been developed for the sequential and specific detection of Cu 2+ and cysteine (Cys)/histidine (His) in pure aqueous medium. The probe Ru-DPA displayed an 'on–off' luminescence response at 610 nm specifically toward Cu 2+, accompanied by a distinct naked-eye luminescence color change from orange-red to colorless. Also, Ru-DPA enabled analysis of Cu 2+ with a detection of limit as low as 0.04 μM. Additionally, the in situ generated Ru-DPA-Cu ensemble detected specifically Cys/His based on the strong affinity for Cu 2+ to Cys and His, giving rise to a significant increase in the MLCT-based luminescence of Ru(II) complex and a relevant chromogenic change from colorless to orange-red. This copper (II) ion competitive-displacement detection strategy offered a good linearity with a low detection limit for Cys at 0.24 μM and His at 1.4 μM under pure aqueous medium. Moreover, Ru-DPA exhibited extremely low cytotoxicity (>90% viability at a concentration range from 20 to 100 μM), excellent membrane permeability and was successfully applied to the luminescence imaging of Cu 2+ and Cys/His both in living bone mesenchymal stem cells (BMSCs) and zebrafish. The results demonstrated the great potential of Ru-DPA for monitoring Cu 2+ and Cys/His in environmental and biological systems. Graphical abstract: A water-soluble and red-emissive ruthenium(II) tris(bipyridine)-based probe for the sequential and highly selective detection of Cu 2+ and cysteine/histidine has been achieved through the competitive displacement reaction. Image 1 Highlights: A new ruthenium(II) complex-based chemosensor was developed. The chemosensor specifically detects Cu 2+ by a distinct naked-eye luminescence color change from orange-red to colorless. The in situ generated Cu(II) ensemble can recognize specifically Cys/His with a restored orange-red luminescence. The chemosensor shows high sensitivity and works in pure aqueous solution. The chemosensor is used for imaging Cu 2+ and cysteine/histidine in living cells and zebrafish.